Who took the cake? - Wurzberg, Robert; Ziefert, Harriet (New York : Sterling, 2005)
Dusty and friends make a cake, eat it, and wash the dishes.
Keywords: Cake -- Juvnenile fiction; Lost articles -- Juvenile fiction; Readers (Primary); Cake -- Fiction; Lost and found possessions -- Fiction; Readers